2008
DOI: 10.1002/gps.2128
|View full text |Cite
|
Sign up to set email alerts
|

An in‐home geriatric programme for vulnerable community‐dwelling older people improves the detection of dementia in primary care

Abstract: An in-home geriatric assessment and management programme for vulnerable older patients improves the detection of dementia and can therefore contribute to overcoming of under-diagnosis of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…20 Among interventions that altered the care pathway, the trial of an in-home assessment of patients' mental wellbeing and functional capacity showed a significant improvement in detection rates. 23 Two studies of case management demonstrated improved management either by providing care more adherent to guidelines, increasing referrals to community services, and increasing anti-cholinesterase prescribing, 24 or by reducing hospital use and consultation rates with physicians, and by decreasing feelings of depression or isolation. 25 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…20 Among interventions that altered the care pathway, the trial of an in-home assessment of patients' mental wellbeing and functional capacity showed a significant improvement in detection rates. 23 Two studies of case management demonstrated improved management either by providing care more adherent to guidelines, increasing referrals to community services, and increasing anti-cholinesterase prescribing, 24 or by reducing hospital use and consultation rates with physicians, and by decreasing feelings of depression or isolation. 25 …”
Section: Discussionmentioning
confidence: 99%
“…41 The service innovation that produced the most benefits adapted the traditional doctorpatient-caregiver paradigm by introducing a multidisciplinary approach. 23 Another noncontrolled pilot study that tested shared (group) medical appointments for patients with dementia, and that demonstrated benefits by enabling collaboration between patients, caregivers, and clinicians, 42 supports this conclusion. These findings are consistent with the arguments of de Lepeleire et al, 43 who proposed that detection could be improved by employing a stepwise strategy, that improving the referral pathway could be more effective than introducing disease-specific guidelines, and that a strong, multidisciplinary approach enables diagnosis.…”
Section: Comparison With Existing Literaturementioning
confidence: 91%
See 2 more Smart Citations
“…4,5 In the Netherlands, an assessment and management program provided to frail older individuals has successfully improved the detection and management of dementia. 6,7 Nurses are an integral part of these home-based care programs and have contributed greatly to their findings.…”
Section: Introductionmentioning
confidence: 99%